Analysis on the evolution of shipping logistics service supply chain market structure under the application of blockchain technology. (August 2022) - Chen, Yujing; Yang, Bin
Abstract: With the digital transformation of the shipping industry, the business potential of shipping companies is gradually expanding. In recent years, shipping companies have begun operating freight forwarding businesses powered by the advantages of cost and network. As a result, their business expansion and gradually occupying the market share of agency services. At the same time, the development requirements of digitization are further highlighted, while the problems of opaque information and inaccurate data in the operation of the shipping logistics service supply chain have become more prominent. Thus, the shipping industry has begun to apply Blockchain Technology (BCT) to the shipping logistics. However, the promotion of BCT, an emerging technology in the shipping logistics service market, is not systematic. The members of the supply chain do not have a deep understanding of it, which have led to changes in market demand. We take the shipping logistics service supply chain composed of shipping companies and freight forwarders as the research object in order to investigate the vertical competition between shipping companies and freight forwarders as well as the impact of BCT application on market structure changes. From the perspectives of freight rate competition and the promotion of BCT, the Stackelberg game theory is applied to create a mathematical model that can be used to discuss the evolution of the shipping logistics service market. The results indicate that, the impact of freight rate competition on market evolution is reduced after the application of BCT. Shipping companies should actively promote BCT to reduce the impact of freight competition on the market. Furthermore, freight forwarders can actively participate in the initial stage of application to increase market demand, and the cost of promoting BCT should be reduced in the later stage.